The Addition of Microencapsulated or Nanoemulsified Bioactive Compounds Influences the Antioxidant and Antimicrobial Activities of a Fresh Cheese - Elizabeth Pérez-Soto; Antonio de Jesús Cenobio-Galindo; Salvador Omar Espino-Manzano; Melitón Jesús Franco-Fernández; Fanny Emma Ludeña-Urquizo; Rubén Jiménez-Alvarado; Andrea Paloma Zepeda-Velázquez; Rafael Germán Campos-Montiel (Molecules, 2021)
The objective of this study was to compare the effects of the incorporation of microcapsules or nanoemulsions with Opuntiaoligacantha on the quality of fresh cheese. Three treatments were established: Control, cheese with microcapsules (Micro), and cheese with nanoemulsion (Nano). The parameters evaluated were physicochemical (moisture, ash, fat, proteins, and pH), microbiological (mesophilic aerobic bacteria, mold–yeast, and total coliforms), functional (total phenols, flavonoids, and antioxidant capacity), and texture (hardness, elasticity, cohesion, and chewiness) during storage for 45 days at 4 °C. The results showed that adding microcapsules and nanoemulsion did not affect the physicochemical parameters of the cheese. Total coliforms decreased in all samples from the first days of storage (Control: 4.23 ± 0.12, Micro: 3.27 ± 0.02, and Nano: 2.68 ± 0.08 Log10 CFU), as well as aerobic mesophiles and mold–yeast counts. Regarding the functional properties, an increase in total phenols was observed in all treatments. The texture profile analysis showed that the addition of microcapsules and nanoemulsion influenced hardness (Control: 8.60 ± 1.12, Micro: 1.61 ± 0.31, and Nano: 3.27 ± 0.37 N). The antimicrobial effect was greater when nanoemulsions were added, while adding microcapsules influenced the antioxidant activity more positively.